Two-Dimensional Pore-Level Simulation of Low-Velocity Filtration Combustion in a Packed Bed with Staggered Arrangements of Discrete Cylinders. Issue 7 (3rd July 2017) - Shi, Junrui; Xiao, Hongxia; Li, Jun; Li, Nan; Xia, Yongfang; Xu, Youning
ABSTRACT: A pore level numerical simulation of filtration combustion in a 2D porous media made of staggered arrangements of discrete cylinders with a diameter of 6 mm was performed. The reaction of methane is described by a single-step first-order Arrhenius type expression, and solid conduction and surface radiation exchange between particles are considered in the model. Numerical simulations are performed with the CH4 /Air mixture velocity of 0.23–0.83 m/s and equivalence ratio of 0.15–0.45. Results show that, for low-velocity filtration combustion, the flame and flow are highly two-dimensional, and that the thickness is the order of magnitude of the cylinder diameter. At the same time, the maximum normalized velocity in the centerline of the burner reaches 11.5–14.5 times the average interstitial gas velocity. Obvious thermal nonequilbrium in the burner for the same phase and interphase are observed except for the inlet and exit zones of the burner, which are far from the reaction zone. The extent of the thermal nonequilbrium varies along the flow direction, and its value is rather small just downstream of the reaction zone. The numerical predictions show qualitative agreements with experimental data available from the literature.